Avaliação ultrassonográfica de endometriose na cicatriz de cesariana: proposta de laudo estruturado e audiovisual - Palheta, Michel Santos (2024)
Introduction: Cesarean scar endometriosis (CSE) is the most common type of extra-pelvic endometriosis, which usually develops after obstetric surgeries. Objective: Describe the ultrasound aspects of CSE and propose a structured and audiovisual report on ultrasound (US) examinations of the abdominal wall. Method: 21 women aged between 20 and 49 years (average of 33 years) were investigated, undergoing US of the abdominal wall, from June 20, 2023, to January 30, 2024, at a diagnostic imaging center in the city of Sobral, in the state of Ceará, Brazil. Results: The main signs and symptoms were pain on palpation (95.23%), cyclical pain (90.47%), palpable mass (85.71%). Endometriosis lesions were located along the path of the cesarean section scar in 100% of cases. The predominant ultrasound appearance was round/oval shape in 61.90% of cases, homogeneously hypoechogenic lesion in 85.71%, poorly defined external limits in 85.71%, and in 100% the lesion was hypovascularized on Doppler and with high tissue stiffness in elastography. The CSEwas in the subcutaneous plane (52.38%), muscular plane (33.33%), in both the subcutaneous and muscular planes (9.52%), infiltrating the muscular fascia (33.33%) and infiltrating pre-peritoneal fat (4.76%). Regarding audiovisual reports, the responses of the doctors interviewed demonstrated a promising scenario, as 100% indicated that the audiovisual report helped in the clinical suspicion of CSE, 100% agreed that the audiovisual report improves the understanding of clinical cases of CSE, and the majority responded that enough to make decisions in patient care. Conclusions: The ultrasonographic characteristics of CSE lesions were a nodular, hypoechogenic, solid and homogeneous lesion, with ill-defined contours, oval or irregular shape, hypovascularized on Doppler and with high tissue stiffness on elastography and the audiovisual report demonstrated clarity, levels of confidence and interactivity.